Exploring the Experience of Novelty When Viewing Creative Adverts: An ERP Study - Zhou, Shujin; Yin, Yue; Yu, Tingting; Stupple, Edward J. N.; Luo, Junlong (Frontiers in Psychology, 2018)
Abstract：The electrophysiological correlates of experiencing novelty in creative advertising were studied in 28 healthy subjects using event-related potentials (ERPs). Participants viewed images that were difficult to interpret until a description was presented providing either a creative description featuring an unexpected description of the image based on the original advertisement, or a normal description, which was a literal description of the image (and served as a baseline condition). Participants evaluated the level of creativity of the description. The results showed that the N2 amplitude was higher for creative descriptions than for normal descriptions across middle and right scalp regions between 240 and 270 ms, most likely reflecting conflict detection. Moreover, creative descriptions demonstrated greater N400 than normal descriptions in a time window between 380 and 500 ms, it is argued that this reflects semantic integration. The present study investigates the electrophysiological correlates of experiencing novelty in advertising with ecologically valid stimuli. This substantially extends the findings of earlier laboratory studies with more artificial stimuli.